STUDENTS' PERCEPTIONS OF TEAMS GAMES TOURNAMENTS IN INCREASING MOTIVATION LEARN ARABIC - Muluk, M. Tajul; Indriana, Dina; Ubaidillah, Ubaidillah (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to determine the perception of students of class VII MTsN 1 Pandeglang towards the use of Teams Games Tournament (TGT) type cooperative learning model in increasing motivation to learn Arabic. The research method used is a quantitative survey with a sample of 88 students selected randomly. Data were collected through a Likert scale questionnaire that had been tested for validity and reliability. The results showed that 92% of respondents had a positive perception of the use of TGT in Arabic language learning, with the majority (47%) strongly agreeing that TGT increased their learning motivation. TGT is considered effective because it makes learning more interesting, fun, and interactive. The model involves learners actively in group games and provides rewards, which is in line with Maslow's hierarchy of needs theory. The study also confirmed that TGT can increase learners' intrinsic motivation, encourage active participation, and change negative perceptions towards learning Arabic. The implication of this study is the enrichment of Arabic language learning techniques with TGT as an effective option, as well as the expansion of educators' perspectives to pay more attention to the psychological aspects of learners. This research provides a valuable contribution to the scientific development of Arabic language education that is more innovative, effective, and relevant to the needs of learners in the modern era.